INFLUENCE OF SALINE DEPOSITS ON THE CONDITIONS OF PETROLEUM GENERATION IN THE ROCKS UNDERLYING THE SALT COMPLEX OF THE NORTHERN PART OF THE PRECASPIAN BASIN - Galushkin Yu.I.; Yakovlev G.E. (My University, 2007)
Numerous studies on the potential of hydrocarbon generation by the rocks of the sedimentary cover of the northern Precaspian Basin are based either on the interpolation of measurements from a relatively sparse boreholes network or on the numerical estimations of the history of development of the hydrocarbon potential under the assumption of a steady temperature gradient both with depth in the sedimentary cover and with time during basin evolution. By the example of sedimentary sections from the northeastern part of the Precaspian Basin, variations in thermal history and petroleum formation conditions were numerically analyzed for the rocks underlying the salt complex of the basin. Variations in the temperature gradient and thermal properties of the rocks with depth and time were accounted for in the modeling. Numerical reconstructions of the thermal and maturation history of sedimentary sections from the basin were used to estimate the influence of evaporite sequences on the thermal history, the maturation level of organic matter, and the hydrocarbon generation potential of the subsalt complex of the basin. The calculations showed that this influence could be significant, but there remained an uncertainty related to the absence of reliable data on the time and rate of salt diapir formation.